Cycling amongst Māori: Patterns, influences and opportunities. (17th November 2020) - Jones, Rhys; Kidd, Bruce; Wild, Kirsty; Woodward, Alistair
Abstract: This paper outlines the results of mixed‐methods research on Māori and cycling. Our findings suggest that Māori cycle at similar rates to Pākehā (NZ European); however conditions may differ, possibly indicating higher levels of "necessity cycling" amongst Māori. Māori experience similar barriers to cycling, including a lack of suitable cycling infrastructure, but these occur against a backdrop of stark social, economic and transport‐related inequities. Particular barriers for Māori may include inflexible work conditions, concerns about neighbourhood safety, inadequate provision for social cycling, and lack of access to places of importance to Māori. We identify potential solutions, including more whānau‐friendly and culturally safe cycling infrastructure, and cycling programmes designed around Māori commitments to whanaungatanga and kaitiakitanga.